Newton and the God of Dominion. Voluntarist Theology illustrated in the concepts of Absolute Space, Absolute time and Universal Gravitation - Ochoa, Felipe (Estudios de Filosofía, 2005)
This paper proposes Voluntarist Theology as an articulator key in order to understand Newton’s scientific and non-scientific work. To avoid the isolation and incongruousness in Newton’s work, this Theology makes possible a integral reading of it that is harmonious. At the same time, Voluntarist Theology carefully considers the specificity of each and every single area that Newton studied such as Physics, Mathematics, prisca sapientia, Alchemy and Theology. Newton’s Voluntarist Theology is illustrated in the concepts of Absolute Space Absolute time and Universal Gravitation.